If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -9)(x + 9)(x + 2) = 0 Reorder the terms: (-9 + x)(x + 9)(x + 2) = 0 Reorder the terms: (-9 + x)(9 + x)(x + 2) = 0 Reorder the terms: (-9 + x)(9 + x)(2 + x) = 0 Multiply (-9 + x) * (9 + x) (-9(9 + x) + x(9 + x))(2 + x) = 0 ((9 * -9 + x * -9) + x(9 + x))(2 + x) = 0 ((-81 + -9x) + x(9 + x))(2 + x) = 0 (-81 + -9x + (9 * x + x * x))(2 + x) = 0 (-81 + -9x + (9x + x2))(2 + x) = 0 Combine like terms: -9x + 9x = 0 (-81 + 0 + x2)(2 + x) = 0 (-81 + x2)(2 + x) = 0 Multiply (-81 + x2) * (2 + x) (-81(2 + x) + x2(2 + x)) = 0 ((2 * -81 + x * -81) + x2(2 + x)) = 0 ((-162 + -81x) + x2(2 + x)) = 0 (-162 + -81x + (2 * x2 + x * x2)) = 0 (-162 + -81x + (2x2 + x3)) = 0 (-162 + -81x + 2x2 + x3) = 0 Solving -162 + -81x + 2x2 + x3 = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| 2x-1+6x=5x-17+x | | -3x-7x= | | 3u-.96=6.3 | | 8m+23-2m= | | (x-9)(x+9)(x+3)=0 | | 4(5y-2)/3+1=5(2y-5)/3-2 | | 5y^2+47y+56=0 | | s/7-3.9=6.1 | | 5/7-3.9=6.1 | | 15-(7-9)/6(9-2)=3/5 | | m=x^2-5x+264 | | 5x^2+5y^2-11xy+1=0 | | 29/40+33/4=x | | 2(x-1)(3x+2)=x+292 | | 29/40+33/4 | | m/9-2.6=5.7 | | 116+1320/160=x | | 2x-2=512 | | 10x-13=14x-75 | | x^2+4y=4 | | 2x-6=64 | | r^2-20=r | | y=-1/3x-1 | | -7.5/4 | | 4e^3x-1=244 | | lnx=4.9 | | 22b=143-33 | | 2a+5a=8b | | y-3=-4(5) | | x^2+2x+40=0 | | 12+34-6=50 | | 12+34-6=40 |